Peranan Qawaid Al-Fiqhiyyah dalam Pencatatan Perkawinan - Noor Izzati Amelia; Vichi Novalia; M. Riyas Rasyid; Lisnawati Lisnawati (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
Qawaid al-Fiqhiyyah are fundamental principles in Islamic law that serve as guidelines for establishing legal rulings, including in the context of marriage registration. Although, in Islam, the validity of a marriage is determined by the fulfillment of its pillars and conditions, marriage registration becomes crucial in state law to ensure legal certainty and provide protection for married couples and their children. The application of fiqh principles such as "Harm must be eliminated" and "Preventing harm takes precedence over obtaining benefits" indicates that marriage registration is necessary to prevent various legal and social issues. Furthermore, this registration aligns with the principle of maslahah (public benefit) in Islamic law, which aims to safeguard the rights of spouses and their offspring. Therefore, although marriage registration is not a requirement for a valid marriage in Islam, from a legal and public welfare perspective, it plays a highly significant role.